2013
DOI: 10.3791/50085
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Tumor Antigen-loaded Mature Dendritic Cells for Immunotherapy

Abstract: While clinical studies have established that antigen-loaded DC vaccines are safe and promising therapy for tumors, their clinical efficacy remains to be established. The method described below, prepared in accordance with Good Manufacturing Process (GMP) guidelines, is an optimization of the most common ex vivo preparation method for generating large numbers of DCs for clinical studies. Our method utilizes the synthetic TLR 3 agonist Polyinosinic-Polycytidylic Acid-poly-L-lysine Carboxymethylcellulose (Poly-IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Human MDDCs were differentiated from monocyte fractions of human PBMCs obtained from healthy volunteer blood donors, as described previously [8,29,30]. Human buffy coats served as the source of monocytes and were obtained from the New York Blood Center (New York, NY, USA).…”
Section: Generation Of Mddcs and Primary DC Isolationmentioning
confidence: 99%
“…Human MDDCs were differentiated from monocyte fractions of human PBMCs obtained from healthy volunteer blood donors, as described previously [8,29,30]. Human buffy coats served as the source of monocytes and were obtained from the New York Blood Center (New York, NY, USA).…”
Section: Generation Of Mddcs and Primary DC Isolationmentioning
confidence: 99%
“…(11,(23)(24)(25). Previous studies have revealed that Tα1 exerts immunomodulatory effects on the maturation, differentiation and function of DCs from murine bone marrow (18,26) and healthy human PB (21).…”
Section: Discussionmentioning
confidence: 99%
“…Patients received 5 doses of 5×10 6 DCs pulsed with combination of rPSMA and rSurvivin (ratio 1 : 1), in each dose and administered as a subcutaneous injection (see study scheme; Fig. 1 Generation of Monocyte-Derived DCs The DC vaccines were generated as previously described by Sabado et al 30) Briefly, 1-3×10 10 peripheral blood mononuclear cells (PBMCs) were collected by a 3 h leukapheresis procedure from each patient, and then placed in a tissue culture flask adherence at a density of 1×10 6 cells/cm 2 in the presence of 1% human serum albumin (Baxter, Deerfield, U.S.A.). After 2 h of incubation at 37°C in 5% CO 2 , non-adherent cells were removed by rinsing with sterile phosphate buffered saline (PBS).…”
Section: Patient Population and Study Designmentioning
confidence: 99%